Clinical cases of management and treatment of women with chemoresistant tuberculosis during pregnancy - Raznatovska, O. M.; Siusiuka, V. H.; Fedorec, A. V.; Pyroh, A. I.; Makurina, H. I.; Разнатовська, Олена Миколаївна; Сюсюка, Володимир Григорович; Федорець, А. В.; Пирог, А. І.; Макуріна, Галина Іванівна; Разнатовская, Е. Н.; Сюсюка, В. Г.; et al. (Запорізький державний медичний університет, 2020)
Importance of chemoresistant tuberculosis (CRTB) is undoubted both in Ukraine and all over the world. Especially alarming fact is that together with high CRTB sickness rate among young working-age people there is the low efficiency of therapy (55 %). Data of many researchers show, that tuberculosis of pregnant women is the reason of many significant complications which make serious maternal and perinatal danger. The problem of CRTB for pregnant woman is especially dangerous because the patient should take antimycobacterial drugs of II grade for a long period and these drugs have teratogenic effect. Purpose. Familiarization of physician-practitioners with the clinical features of the course and treatment of CRTB in women during pregnancy. Materials and methods. 4 clinical cases of own observations of the course and treatment of CRTB in women during pregnancy were described. Results. Among our investigations the artificial termination of pregnancy was inevitable in 3 of 4 presented clinical cases. The first patient had tubal pregnancy. The second patient: together with medical indications for artificial termination of pregnancy (multiresistant tuberculosis, unstable position of fetus), the absence of the patient’s tendency for treatment of multiresistant tuberculosis and problem social factor were observed. The patient informed that pregnancy was undesirable. The third patient had polyresistant tuberculosis and generalized destructive tuberculosis in lungs and besides the artificial termination of preg¬nancy was also her decision. The fourth patient had medical indications for artificial termination of pregnancy (multiresistant tuberculosis, negative clinical and radiological dynamics) but she refused. With regard to refusal antimicrobial therapy was corrected and aminoglycosides were excluded. The patient was responsible as to her own health and treatment of multiresistant tuberculosis. Under complex simultaneous control of phthisiatrician, obstetrician-gynecologist and neonatologist she terminated complete course of antimicrobial therapy with successful treatment result and gave birth to healthy baby. Conclusions. Summarizing our own observations of the pregnant patients with CRTB the following conclusion can be made: if patients with CRTB have tendency to antimicrobial therapy and desire to give birth the positive results such as CRTB treatment and delivery of healthy baby will be obtained under complex simultaneous control of phthisiatrician, obstetrician-gynecologist and neonatologist. Беззаперечною нині є актуальність хіміорезистентного туберкульозу (ХРТБ) в Україні й усьому світі. Особливе занепокоєння викликає те, що на тлі високого захворювання на ХРТБ молодого працездатного населення відзначають низьку ефективність лікування (55 %). Результати багатьох досліджень показують, що туберкульоз у вагітних жінок – причина багатьох серйозних ускладнень, які становлять серйозну материнську та перинатальну небезпеку. Особливо небезпечною є проблема ХРТБ у вагітної, оскільки пацієнтці необхідно тривало приймати антимікобактеріальні препарати ІІ ряду, що мають значущий тератогенний вплив. Мета роботи – ознайомлення фахівців-практиків із клінічними особливостями перебігу та лікування ХРТБ у жінок під час вагітності. Матеріали та методи. Описали 4 клінічні випадки власних спостережень перебігу та лікування ХРТБ у жінок під час вагітності. Результати. З-поміж 4 наведених клінічних випадків у 3 жінок штучне переривання вагітності було неминучим. В однієї пацієнтки була трубна вагітність. В іншої жінки на тлі медичних показань до штучного переривання вагітності (мультирезистентний туберкульоз, нестійке положення плоду) визначали відсутність схильності до лікування мультирезистентного туберкульозу та несприятливий соціальний фактор; крім того, сама пацієнтка відзначила, що вагітність небажана. У третьої пацієнтки діагностували полірезистентний туберкульоз і поширений деструктивний туберкульоз у легенях; жінка сама мала бажання штучно перервати вагітність. У четвертої пацієнтки до штучного переривання вагітності були медичні показання (мультирезистентний туберкульоз, негативна клінічно-рентгенологічна динаміка), від якого вона відмовилася. Враховуючи відмову, скорегували схему антимікобактеріальної терапії зі скасуванням аміноглікозидів. Хвора відповідально ставилася до власного здоров’я та лікування мультирезистентного туберкульозу. Під комплексним одночасним контролем фтизіатра, акушера-гінеколога та неонатолога завершила повний курс антимікобактеріальної терапії, у результаті мала успішне лікування та народила здорову дитину. Висновки. Підсумовуючи власні клінічні спостереження за вагітними, які хворі на ХРТБ, можна зробити висновок: за наявності у них схильності до антимікобактеріальної терапії і бажання народити дитину, під комплексним одночасним контролем фтизіатра, акушера-гінеколога та неонатолога можна досягти позитивних результатів – лікування ХРТБ і на¬родження здорової дитини. Бесспорна актуальность химиорезистентного туберкулеза (ХРТБ) в Украине и в мире. Особенно настораживает то, что на фоне высокой заболеваемости ХРТБ молодого трудоспособного населения отмечают низкую эффективность лечения (55 %). Результаты многих исследований показывают, что туберкулез у беременных – причина многих серьезных осложнений, которые являются серьезной материнской и перинатальной опасностью. Особенно опасна проблема ХРТБ у беременной, поскольку пациентке необходимо длительно принимать антимикобактериальные препараты II ряда, которые имеют значительное тератогенное влияние. Цель работы – ознакомление специалистов-практиков с клиническими особенностями течения и лечения ХРТБ у женщин во время беременности. Материалы и методы. Описаны 4 клинических случая собственных наблюдений течения и лечения ХРТБ у женщин во время беременности. Результаты. Из 4 представленных клинических случая у трех женщин искусственное прерывание беременности было неизбежным. У одной пациентки была трубная беременность. У другой женщины на фоне медицинских показаний к искусственному прерыванию беременности (мультирезистентный туберкулез, неустойчивое положение плода) установлено отсутствие приверженности к лечению мультирезистентного туберкулеза и неблагоприятный социальный фактор; кроме того, сама пациентка указывала, что беременность нежелательная. У третьей пациентки диагностировали полирезистентный и распространенный деструктивный туберкулез в легких, женщина сама потребовала искусственного прерывания беременности. У четвертой пациентки для проведения искусственного прерывания беременности были медицинские показания (мультирезистентный туберкулез, отрицательная клинико-рентгенологическая динамика), от которого она отказалась. Учитывая отказ, проведена коррекция схемы антимикобактериальной терапии с отменой аминогликозидов. Больная ответственно относилась к собственному здоровью и лечению мультирезистентного туберкулеза. Под комплексным одновременным контролем фтизиатра, акушера-гинеколога и неонатолога завершила полный курс антимикобактериальной терапии, результат которой – успешное лечение и рождение здорового ребенка. Выводы. Подытоживая собственные клинические наблюдения за беременными, больными ХРТБ, можно сделать вывод: при наличии приверженности к антимикобактериальной терапии у беременных и желания родить ребенка, под комплексным одновременным контролем фтизиатра, акушера-гинеколога и неонатолога можно достичь положительных результатов – лечения ХРТБ и рождения здорового ребенка.
Клінічні випадки ведення та лікування жінок, які хворі на хіміорезистентний туберкульоз під час вагітності
Клинические случаи ведения и лечения женщин, больных химиорезистентным туберкулезом во время беременности
Разнатовська О. М. - ORCID ID: 0000-0003-2252-9063
Keywords: chemoresistant tuberculosis; pregnancy; хіміорезистентний туберкульоз; вагітність; химиорезистентный туберкулез; беременность